Depression as a Glial-Based Synaptic Dysfunction - Rial, Daniel; Lemos, Cristina; Pinheiro, Helena; Duarte, Joana M.; Gonçalves, Francisco Q.; Real, Joana I.; Prediger, Rui D.; Gonçalves, Nélio; Gomes, Catarina A.; Canas, Paula M.; Agostinho, Paula; Cunha, Rodrigo A. (Frontiers in Cellular Neuroscience, 2016)
Recent studies combining pharmacological, behavioral, electrophysiological and molecular approaches indicate that depression results from maladaptive neuroplastic processing occurring in defined frontolimbic circuits responsible for emotional processing such as the prefrontal cortex, hippocampus, amygdala and ventral striatum. However, the exact mechanisms controlling synaptic plasticity that are disrupted to trigger depressive conditions have not been elucidated. Since glial cells (astrocytes and microglia) tightly and dynamically interact with synapses, engaging a bi-directional communication critical for the processing of synaptic information, we now revisit the role of glial cells in the etiology of depression focusing on a dysfunction of the ‘quad-partite’ synapse. This interest is supported by the observations that depressive-like conditions are associated with a decreased density and hypofunction of astrocytes and with an increase microglia ‘activation’ in frontolimbic regions, which is expected to contribute for the synaptic dysfunction present in depression. Furthermore, the traditional culprits of depression (glucocorticoids, biogenic amines, BDNF) affect glia functioning, whereas antidepressant treatments (SSRIs, electroshock, deep brain stimulation) recover glia functioning. In this context of a quad-partite synapse, systems modulating glia-synapse bidirectional communication - such as the purinergic neuromodulation system operated by ATP and adenosine - emerge as promising candidates to “re-normalize” synaptic function by combining direct synaptic effects with an ability to also control astrocyte and microglia function. This proposed triple action of purines to control aberrant synaptic function illustrates the rationale to consider the interference with glia dysfunction as a mechanism of action driving the design of future pharmacological tools to manage depression.